Comparative Perspectives on Curriculum Development: The Societal and Natural Educational Theories of Ibn Khaldun and Jean-Jacques Rousseau - Dariyanto, Dariyanto; Pratama, Dio Septa (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This article examines the comparative perspective between Ibn Khaldun's social education theory and Jean-Jacques Rousseau's natural education theory, focusing on their implications for curriculum development. The background of this research stems from the fundamental differences in the thinking of these two figures, each offering a unique approach to the goals of education. Ibn Khaldun views education as a tool for maintaining social order and creating individuals who align with societal values. At the same time, Rousseau emphasizes individual freedom and the natural development of children within the educational process. This study aims to identify the similarities, differences, and relevance of both theories in the context of contemporary education. The methodology used in this research is a qualitative approach with a comparative analysis of the literature related to these two theories. The study finds that, despite their differing focuses, both contribute significantly to the development of a holistic curriculum that accommodates both societal needs and personal development of students. Ibn Khaldun emphasizes the importance of instilling social and religious values, whereas Rousseau emphasizes individual freedom and experiential learning. The theoretical contribution of this research lies in the integration of both approaches within educational thought, while its practical contribution is in its ability to provide insights to policymakers in designing a more balanced curriculum that is relevant to contemporary global challenges.